The local, the global, and the self : an ethnographic account of a community Computer Centre in Carnarvon, Northern Cape, and its significance for its users’ sense of self and their place in the world - Van der Hoef, Monique (Stellenbosch : Stellenbosch University, 2017)
Thesis (MA)--Stellenbosch University, 2017.